Effectiveness of various irrigation protocols for the removal of calcium hydroxide from artificial standardized grooves - GOKTURK, Hakan (J Appl Oral Sci, 2017)
OBJECTIVE: The aim of this study was to investigate the ability of laser-activated irrigation (LAI), XP-endo Finisher, CanalBrush, Vibringe, passive ultrasonic irrigation (PUI), and conventional syringe irrigation systems on the removal of calcium hydroxide (CH) from simulated root canal irregularities. MATERIAL AND METHODS: The root canals of one hundred and five extracted single-rooted teeth were instrumented using Reciproc rotary files up to size R40. The teeth were split longitudinally. Two of the three standard grooves were created in the coronal and apical section of one segment, and another in the middle part of the second segment. The standardized grooves were filled with CH and the root halves were reassembled. After 14 days, the specimens were randomly divided into 7 experimental groups (n=15/group). CH was removed as follows: Group 1: beveled needle irrigation; Group 2: double side-vented needle irrigation; Group 3: CanalBrush; Group 4: XP-endo Finisher; Group 5: Vibringe; Group 6: PUI; Group 7: LAI. The amount of remaining CH in the grooves was scored under a stereomicroscope at 20× magnification. Statistical evaluation was performed using Kruskal–Wallis and Bonferroni-Correction Mann–Whitney U tests. RESULTS: Groups 1 and 2 were the least efficient in eliminating CH from the grooves. Groups 6 and 7 eliminated more CH than the other protocols; however, no significant differences were found between these two groups (P>.05). CONCLUSIONS: Nevertheless, none of the investigated protocols were able to completely remove all CH from all three root regions. LAI and PUI showed less residual CH than the other protocols from artificial grooves.